EFFECT OF WEED MANAGEMENT ON GROWTH, YIELDS, WEED INDICES AND SOIL WEED SEEDBANK IN RABI FENNEL (FOENICULUM VULGARE) - B. S. GOHIL; R. K. MATHUKIA; S. K. CHHODAVADIA; V. K. DOBARIYA; R. M. SOLANKI (The Bioscan, 2015)
A field experiment was conducted during rabi season of 2011-12 at Instruction Farm, Junagadh Agricultural University, Junagadh – 362001 (Gujarat) on clayey soil to find out most effective method of weed control and to manage weed seedbank in rabi fennel. Results revealed that, significantly the higher plant height (153.1 cm), number of branches/plant (7.1), number of umbels/plant (12.7), number of seeds/umbellate (25.5), test weight (7.30 g), seed weight/plant (31.10 g) and seed (1841 kg/ha) and stover (4512 kg/ha) yields of fennel were recorded with weed free treatment, which was at par with pre-emergence (PRE) application of pendimethalin 0.90 kg/ha + post-emergence (POE) application of fenoxaprop-ethyl 75 g/ha at 45 DAS, pendimethalin PRE +hand weeding (HW) at 45 DAS and HW twice at 15 and 45 DAS. Besides weed free and HW twice treatments, lowest weed density and dry weight of weeds at harvest recorded with PRE of pendimethalin + HW (84 kg/ha), which was comparable to PRE pendimethalin + POE fenoxaprop-ethyl (196 kg/ha), PRE pendimethalin + POE oxadiargyl (104 kg/ha). Due to less cultivation cost as compared to weed free, these treatments also exhibited highest net returns (Rs. 81,442 and 81,993) and B : C ratio (3.21 and 3.22) as a result of lower weed index (0.91 and 0.52%) and higher weed control efficiency (93.31 and 84.30%), respectively. The highest depletion of weed seedbank (65%) was observed with pendimethalin + HW. So for effective management of weeds and weed seedbank along with better growth, yield attributes and profitable production of rabi fennel can be obtained by keeping the crop weed free throughout crop period or HW twice or PRE pendimethalin + HW or PRE pendimethalin + POE fenoxaprop-ethyl.